Muscle oxygen saturation and heart rate responses to high-intensity interval training during running and cycling: 2 case studies - Wolff, L.; Capello, K.; Kantor, M.; Pettitt, R.; Dexheimer, J. (The Journal of Strength and Conditioning Research, 2021)
The critical speed or critical power (CS/CP) concept has been used to prescribe individualized training. Recently, the 3-minute all-out exercise test (3 MT) was validated to calculate CS/CP and the finite capacity for exercise > CS/CP, known as distance prime (D') or work prime (W'), for running and cycling, respectively. Using these parameters, precise high-intensity interval training (HIIT) prescriptions can be established. A moderate correlation has been observed between heart rate (HR) and skeletal muscle oxygen (SmO2) during incremental exercise such that when HR increases, SmO2 decreases until reaching maximal exertion. We are unaware of studies investigating the relationship between HR and SmO2 during HIIT intervals. Purpose: The purpose of these case studies was to examine SmO2 and HR responses to HIIT intervals using the CS/CP concept. Methods: Each subject, a competitive distance runner (female, 23 years, 165 cm, 54 kg, 20.4%BF, Vo2peak: 53.5 ml/kg/min; HRmax: 199 bpm; SmO2min: 5.2%) and recreational-cyclist (male, 49 years, 173 cm, 91 kg, 23%BF, Vo2peak: 34.05 ml/kg/min; HRmax: 167 bpm; SmO2min: 18.8%) completed mode-specific, customized graded exercise tests (GXT) and 3 MT. Measures of gas exchange threshold (GET), peak maximum oxygen uptake (Vo2peak), HR (HRmax), and minimum SmO2 (SmO2min) were determined. The heavy-intensity HIIT bouts consisted of 3 × 3 minute bouts at 50% of the intensity evoking GET and CS/CP. The severe-intensity HIIT bouts consisted of 3 × 60% D'/W' depletion bouts for 3 minutes. Results: HR and SmO2 values for the runner are depicted in Figure 1 below. Take notice of the delayed steady-state in the heavy domain whereas in the severe domain, near HRmax and SmO2min were obtained at the end of the third interval. Similar results were demonstrated with cycling, as by the third interval in the severe domain, the maximal HR achieved was 167 bpm and minimum SmO2 achieved was 18.8%, consistent with the GXT results. Conclusions: The data collected displayed an inverse relationship between HR and SmO2. Furthermore, exercise performed in the severe domain similarly matched HR and SmO2 values found during the GXT, whereas these values reached a steady-state during intervals performed in the heavy domain of exercise. Practical Applications: The relationship between HR and SmO2 points to the use of SmO2 as a surrogate measure of exercise intensity, thereby informing training intensities during individualized HIIT intervals. Therefore, near-infrared spectroscopy measures of SmO2 at the muscular level may be used to monitor exercise intensity above and below CS/CP to better improve exercising performance.